2016
DOI: 10.1016/j.foodchem.2014.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of animal age and trimming practices on the physical composition of Bonsmara beef

Abstract: Increased economic incentive for producing young and leaner carcasses, as well as demand for lean meat from progressively health conscious consumers, are considered drivers for change in carcass composition over time. Furthermore, many retailers trim visible fat from meat to various degrees and consumers increasingly remove visible fat from meat prior to, or after, cooking.The objective of this study was to determine the composition of South African Bonsmara beef from four age groups from different production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Growth stage had influenced the marbling development in longissimus muscle from beef cattle (Kern et al 2014). After trimming process, the marbling perimeter value of 18 months beef was significantly different from that of 54 months beef or 72 months beef (Hall et al 2016). Pflanzer and de Felicio (2011) analyzed the intramuscular fat content of rib steaks of Nellore steer (grouped by physiological age, 2, 4 or 6 permanent incisors) using chemical method.…”
Section: Resultsmentioning
confidence: 99%
“…Growth stage had influenced the marbling development in longissimus muscle from beef cattle (Kern et al 2014). After trimming process, the marbling perimeter value of 18 months beef was significantly different from that of 54 months beef or 72 months beef (Hall et al 2016). Pflanzer and de Felicio (2011) analyzed the intramuscular fat content of rib steaks of Nellore steer (grouped by physiological age, 2, 4 or 6 permanent incisors) using chemical method.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the nutritional composition of beef showed that it has an acceptable composition because the dry matter, ash, total protein and total fat contents are within the recommended range for beef [34] [35]. Indeed, the chemical composition of beef is variable [36] [37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…This difference being rather tenuous, it is not astonishing that the positive correlation between intramuscular fat and meat quality traits (Park et al, 2000;Kim and Lee, 2003) was not found in the present study. Indeed, although increase in marbling is associated with increase in consumer preference due to increase in juiciness Strydom, 2011a and2011b;Ngapo et al, 2013), consensus on the increase in tenderness is older animals due to marbling has not been reached (Hall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%